Peran Kurator Terhadap Perubahan Anggaran Dasar Pada Perseroan Pasca Putusan Pailit - Ifa Agustina Eka Ismanto (Universitas Sains dan Teknologi Komputer, 2024)
A limited liability company cannot fulfill its obligations in accordance with a decision that has been made by the court, therefore the company loses its right to control and manage its assets. The bankruptcy law and the suspension of debt payment obligations explains that a curator is a court-ordered inheritance authority or individual who is responsible for managing bankruptcy assets under the supervision of a judge. In the context of company bankruptcy, the curator is obliged to clear up all bankruptcy assets and keep related documents. This article discusses the legal consequences that arise for limited companies after being declared bankrupt by a judge's decision and also the role of the curator in changing the company's articles of association after being declared bankrupt by a court decision.